حظوظ الخصوصيات التراثية في المحافظة على الهوية الثقافية في زمن العولمة - زايدي, فتيحة; مجدوب, فائزة (جامعة الوادي - University of Eloued, 2019)
أن مسألة الهوية في الجزائر تمثل إشكالية قصوى ضمن فسيفساء المشهد الثقافي وخضم الثورة الاتصالية والتكنولوجية مع مبدأ تعدد الثقافات مطلب مفروض في العالم و حتمية الانصهار في الثقافة المعولمة والمهيمنة لكونها أمر محتم؛ فهي لا تعترف بالحدود الوطنية للدولة ولا بالحدود الشخصية للأفراد؛ وعليه تعد قضية الهوية الثقافية قضية إشكالية وهنا تبرز مسألة الماضي القومي والوطني المكتسب في شكل التراث كمرتكز لا بد من المحافظة عليه باعتباره الوجه الحقيقي المعبر عن الهوية الثقافية من جراء التراكمات التاريخية وبين مطلب تغييره أو تنوعه ودخوله حيز الانفتاح لأجل مسايرة متطلبات العولمة وما تحتويه من إغراءات، ولعل ما يزيد من تعقيد هذه الإشكالية ويؤزمها هو تلبسها بالطابع الديني، والإيديولوجي، منه انبثقت مجموعة الأسئلة أهمها: ما هي حظوظ الخصوصيات التراثية في المحافظة على الهوية الثقافية في زمن العولمة؟ وما حقيقة هويتنا بين معطيات الأسلمة، والعروبة والعولمة؟ The issue of identity in Algeria is a fundamental problem within the mosaic of the cultural scene; And the midst of the communication and technological revolution with the principle of multiculturalism is a requirement imposed in the world, And the inevitability of fusion in the globalized and dominant culture as it is inevitable; It does not recognize the national borders of the state or the personal borders of individuals. Therefore, the issue of cultural identity is problematicHere, the issue of the national and national past acquired in the form of heritage appears as an anchor that must be preserved as the true expression of cultural identity as a result of historical accumulations and between the demand for its change or its diversity and its entry into the space of openness in order to keep pace with the requirements of globalization and the temptations it contains Perhaps what complicates and harms this problem is its religious and ideological character, From it emerged a set of questions, the most important of which are: What are the chances of heritage peculiarities in preserving the cultural identity in the era of globalization? What is the truth about our identity between the facts of Islamization, Arabism and globalization?
مقال بمجلة السراج في التربية وقضايا المجتمع . مج 03 ع02. جوان 2019 . جامعة الوادي
Keywords: التراث؛ الثوابت الحضارية؛ الهوية الثقافية؛ العولمة; Heritage, Civilization constants, Cultural identity, Globalisation